2001
DOI: 10.1099/00207713-51-6-2113
|View full text |Cite
|
Sign up to set email alerts
|

Comparative sequence analysis of a recA gene fragment brings new evidence for a change in the taxonomy of the Lactobacillus casei group.

Abstract: T form a single phylogenetic group. The taxonomic status of species and strains at issue is discussed. Keywords : Lactobacillus casei, recA, taxonomyLactobacillus casei and related species include phenotypically and genetically heterogeneous strains able to colonize various natural and man-made environments (Vescovo et al., 1995). Many strains are currently employed as probiotics or mixed cultures for dairy products. Despite its importance for the food industry, the taxonomy of the L. casei group is still uncl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
53
1
10

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 41 publications
(41 reference statements)
6
53
1
10
Order By: Relevance
“…Furthermore, recent genotypic evidence (Mori et al, 1997 ;Tynkkynen et al, 1999 ;Chen et al, 2000 ;Felis et al, 2001) strongly supports previous indications (Mills & Lessel, 1973 ;Dellaglio et al, 1975Dellaglio et al, , 1991Dicks et al, 1996) that strains ATCC 393 and ATCC 15820 are members of the same taxon. Even though the valid status of the species Lactobacillus zeae was recognized only in 1996 (Dicks et al, 1996), the misidentified strain ATCC 393 is closely related to the type strain of this species.…”
supporting
confidence: 70%
See 2 more Smart Citations
“…Furthermore, recent genotypic evidence (Mori et al, 1997 ;Tynkkynen et al, 1999 ;Chen et al, 2000 ;Felis et al, 2001) strongly supports previous indications (Mills & Lessel, 1973 ;Dellaglio et al, 1975Dellaglio et al, , 1991Dicks et al, 1996) that strains ATCC 393 and ATCC 15820 are members of the same taxon. Even though the valid status of the species Lactobacillus zeae was recognized only in 1996 (Dicks et al, 1996), the misidentified strain ATCC 393 is closely related to the type strain of this species.…”
supporting
confidence: 70%
“…tolerans. (3) On the basis that the species Lactobacillus casei has no type strain (see Request 1), we propose strain ATCC 334 as the neotype, since it has been already proposed (Dellaglio et al, 1991 ;Dicks et al, 1996), supported (Mori et al, 1997 ;Tynkkynen et al, 1999 ;Chen et al, 2000 ;Felis et al, 2001) and used as a reference strain (Yoon et al, 2000 ;Cai et al, 1999 ;Morlon-Guyot et al, 1998) (Rule 19). Furthermore, strain LMG 9191 T may be retrieved as the type strain of the subspecies Lactobacillus casei subsp.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As cepas de Lactobacillus casei/paracasei têm sido amplamente estudadas com relação a suas propriedades promotoras à saú-de, sendo freqüentemente empregadas como probióticos em alimentos industrializados (Stiles, Holzapfel, 1997;Felis et al, 2001;Itsaranuwat et al, 2003;Médici et al, 2004;Vásquez et al, 2005).…”
Section: Introductionunclassified
“…In view of its demonstrated effectiveness, sequence analysis of protein-coding genes (e.g., tuf genes) as alternative phylogenetic markers could be added to the arsenal of rRNA sequence databases and to the relatively small groEL (16) and recA (9,22) sequence databases. It has been shown that species having 70% or greater DNA similarity (at the DNA-DNA hybridization or reassociation level) possess in fact more than 97% 16S rDNA sequence identity (43).…”
Section: B Animalis-b Lactis B Longum-b Infantis and L Johnsonmentioning
confidence: 99%